Improving energy efficiency in state-funded facilities through the development and use of a simplified energy audit procedure - Pierson, Kimberly D. (Kansas State University, 2012)
Over the past few years, state governments and entities have become concerned with energy consumption and efficiency at their facilities. The Department of Energy has become increasingly involved in energy code enforcement, and has established initiatives to help states monitor and improve energy consumption. In order to reduce energy consumption and increase building efficiency, facilities must be compared to a baseline building and changes made accordingly. The thesis objectives are to establish a process that all states and state-funded facilities can follow that determines the baseline, establish an energy auditing procedure, and recommend monitoring techniques. In addition, this report documents a procedure developed to make recommendations for improvements and select building and equipment upgrades based and return on investment calculations. The procedures and processes established are designed so that any employee, especially non-engineers, can accomplish changes that will improve facility energy efficiency. In order to develop simplified energy auditing procedures for large and dispersed organizations, a literature review of prevalent energy codes and standards was conducted, as well as documents outlining energy audit procedures. An energy audit workbook outlining a simplified auditing procedure was created. Six KDOT facilities were audited using the procedure as part of the case study. The audit results were then used to determine practical economic calculations and determine viable improvements that reduce energy consumption. As a result of this research and case study, a simplified energy audit procedure was created. This procedure was developed to include selecting a baseline of requirements, conducting an energy audit, and selecting viable improvements using economics. All of these procedures are able to be executed by any state employee, specifically those at the facilities who may not be engineers.
Keywords: Energy efficiency; Energy audit; Architectural engineering (0462); Energy (0791); Engineering (0537)